Current Challenges to the United States’ AIDS Drug Assistance Program and Possible Implications of the Affordable Care Act - Kathleen A. McManus; Carolyn L. Engelhard; Rebecca Dillingham (AIDS Research and Treatment)
AIDS Drug Assistance Programs, enacted through the Ryan White Comprehensive AIDS Resources Emergency Act of 1990, are the “payer of last resort” for prescription medications for lower income, uninsured, or underinsured people living with HIV/AIDS. ADAPs face declining funding from the federal government. State funding of ADAP is discretionary, but some states increased their contributions to meet the gap in funding. The demand for ADAP support is increasing as people living with HIV are living longer; the antiretroviral therapy (ART) guidelines have been changed to recommend initiation of treatment for all; the United States is increasing HIV testing goals; and the recession continues. In the setting of increased demand and limited funding, ADAPs are employing cost containment measures. Since 2010, emergency federal funds have bailed out ADAP, but these are not sustainable. In the coming years, providers and policy makers associated with HIV care will need to navigate the implementation of the Affordable Care Act (ACA). Lessons learned from the challenges associated with providing sustainable access to ART for vulnerable populations through ADAP should inform upcoming decisions about how to ensure delivery of ART during and after the implementation of the ACA.